Clinicopathological characteristics of lung cancer in patients with systemic sclerosis. (7th September 2020) - Chen, Minjiang; Liu, Xiaoyan; Xu, Yan; Zhou, Qing; Shi, Yuequan; Zhang, Dongming; Liang, Hongge; Zhao, Jing; Zhong, Wei; Wang, Mengzhao
Abstract: Background and objectives: Systemic sclerosis (SSc) is a connective tissue disorder (CTD) associated with an increased risk of malignancy including lung cancer (LC). Our objective was to provide a description of demographics and clinicopathological characteristics of LC patients with SSc. Methods: Lung cancer patients with SSc admitted to Peking Union Medical College Hospital from January 2000 to August 2017 were reviewed. Demographic and clinicopathologic data were collected. Results: Of the 12 cases included in our study, all were female. No patients had a history of smoking. The most common histological type was adenocarcinoma, followed by squamous cell carcinoma and small‐cell carcinoma. No driver mutation was identified in the five patients undergoing genetic testing. Eight patients had interstitial lung disease (ILD). Six were manifested as nonspecific interstitial pneumonia (NSIP) and two as usual interstitial pneumonia (UIP). Four (33.3%) patients underwent surgical resection. Among them, two had ILD with a normal preoperative pulmonary function tests (PFT). Eight (66.7%) patients received chemotherapy. Radiotherapy was administered in only one (8.3%) patient. No grade 3/4 adverse events were documented. Conclusion: The predominance of female patients in our study is different from that reported in general lung cancer patients. A high proportion of patients has SSc‐ILD, including NSIP and UIP. Surgery or radiotherapy could still be considered in carefully selected patients with ILD.